The United States and its diplomatic struggle to abort Britain's conscription in international maritime activities (1790-1815) - Binh, Nguyen Tuan; Nam, Le Thanh; Vinh, Vo Xuan; Thao, Bui Thi; Hiep, Tran Xuan (International Journal of Innovative Research and Scientific Studies, 2025)
This article focuses on examining the effects of Britain’s conscription regime on the international maritime activities of the United States. Conscription is a regime imposed by the Royal Navy on many foreign-flagged ships operating on the ocean, including American ships. The existence of this regime in international maritime activities has created a challenge for the United States, a country with ambitions to build fleets to trade with other countries on the ocean. To protect foreign trade activities, national honor, and status, the United States has deployed many different diplomatic methods with the United Kingdom. The United States' diplomatic struggle over the issue of conscription has lasted nearly a quarter of a century since its founding. A series of measures, from economic to military, have been applied and implemented by the administrations of American presidents to force the British authorities to lift the imposition of conscription on American-flagged ships. Based on reference sources and the historical research method combined with the international relations research method, the article analyzes the diplomatic struggle of the United States to abolish Britain’s conscription in international maritime activities.